PENINGKATAN EFISIENSI TATA LETAK RUANG PRODUKSI PADA IHRISH CREATIVE STUDIO MELALUI PENDEKATAN ERGONOMI DAN LEAN MANUFACTURING - Triyono Triyono; Rizki Dwi Ardika Rizki; Eko Surojo; Nurul Muhayat; Teguh Triyono; Sukmaji Indro Cahyono (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to improve the efficiency of production space at Ihrish Creative Studio through an ergonomics and lean manufacturing approach. The study was conducted using direct observation, interviews, workflow analysis, and redesign of the production layout. The implementation results showed a reduction in production material movement time from an average of 14 minutes to 5–6 minutes. This increase in efficiency resulted in an increase in daily production output of up to ±30%, as well as a reduction in operational costs through time and energy savings. The application of ergonomic principles also increased comfort and safety at work, as demonstrated by positive feedback from workers. In addition, the new layout also strengthened the studio's social function as a training and community empowerment center. This study confirms that the integration of ergonomics and lean manufacturing is effective in addressing space limitations in micro-enterprises, while strengthening operational and social sustainability.